Relation between medical sociology and sociology of ageing or later life. A new challenges, social expectations and dilemmas - Tobiasz-Adamczyk, Beata (Anthropological Review, 2015)
Medical sociology has not paid special attention to observed demographic changes associated with the “greying of societies”. Lack of interest in ageing has resulted in the necessity to develop a new subdiscipline – sociology of aging. The evolution of this subdiscipline has been described in relation to social gerontology. Theories of aging (healthy, successful) have been presented in relation to new changes. Dilemmas and intractable problems focus on prejudices concerning the older persons, gender-related differences in the quality of life in older age, elderly abuse, and quality of life in mentally ill old people as well as other issues.